In vivo investigation of antihyperalgesic and antinociceptive effects of peat formulations - Zagorchev Plamen Ivanov; Apostolova Elisaveta Georgieva; Pilicheva Bissera Asenova; Draganova-Filipova Milena Nenkova; Kokova Vesela Yulieva; Lukanov Julian Borisov (Acta Pharmaceutica)
The aim of this study is to evaluate the antihyperalgesic and antinociceptive effects of two formulations containing peat water extracts using a model of carrageenan-induced hyperalgesia, combined with a test with a mechanical stimulus, and a hot plate test. Rats were divided into seven groups (n = 6) and received local treatment with two peat formulations and two diclofenac formulations dissolved in carbopol gel and Wolff® basis creme, respectively. Carbopol gel, Wolff® basis creme and 0.9 % NaCl without tested substances were used as controls. Both peat formulations exerted an unambiguous antihyperalgesic effect 60 minutes after the treatment. In the hot plate test, the rats treated with the Wolff® basis creme peat formulation showed a tendency to prolonged latency on the first hour. The results could be explained by partial activation of peripheral α2-adrenoceptors and the possible COX-2 suppressive activity.